2018
DOI: 10.1093/annweh/wxy070
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Mycotoxins: Current Knowledge and Prospects

Abstract: Occupational exposure to mycotoxins is supposedly very frequent, but it is rarely reported in the scientific literature. Several recent studies described occupational exposure to the aflatoxin B1 (AFB1) mycotoxin in different occupational settings. Previously, exposure to other mycotoxins was shown in the animal husbandry and food processing sectors, confirming that occupational exposure cannot be negligible. However, no guidelines or standard methodologies are available for helping occupational hygienists to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 73 publications
(86 reference statements)
0
51
0
Order By: Relevance
“…Air samples and EDC fungal counts followed the same trend than a previous study, which explored fungal concentrations in Portuguese bakeries [41]. However, regarding settled dust, in this current study, besides mycotoxin detection, fungal isolates were observed using culture-based methods and were detected by qPCR (Aspergillus section Fumigati), whereas in the Portuguese study, only mycotoxins were detected, which emphasizes the importance of measuring both fungi and mycotoxins, as the absence of one (fungi/mycotoxins) is not a surrogate for the absence of the other [42].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Air samples and EDC fungal counts followed the same trend than a previous study, which explored fungal concentrations in Portuguese bakeries [41]. However, regarding settled dust, in this current study, besides mycotoxin detection, fungal isolates were observed using culture-based methods and were detected by qPCR (Aspergillus section Fumigati), whereas in the Portuguese study, only mycotoxins were detected, which emphasizes the importance of measuring both fungi and mycotoxins, as the absence of one (fungi/mycotoxins) is not a surrogate for the absence of the other [42].…”
Section: Discussionmentioning
confidence: 71%
“…This can happen because of the re-suspension of settled dust, and also from exposure as a result of the high volumes of flour used by the workers in this sector on a daily basis [2,3]. There is currently a knowledge gap concerning the approach, which should be used to accomplish a suitable risk assessment methodology for mycotoxins, as toxicokinetics and toxicodynamics data for mycotoxins from exposure routes other than ingestion are lacking [42]. The mycotoxin contamination of flour can vary depending on where the wheat is harvested, and is thought to be now impacted by climate change, as the cereals used for flour production can be contaminated by different mycotoxins or with a different intensity [40,41,62].…”
Section: Discussionmentioning
confidence: 99%
“…12 Occupational exposure can happen by inhalation or by dermal contact, resulting in exposure by ingestion or through absorption. 11 Mycotoxins are not volatile, so airborne dust and fungal spores and fragments act as carriers of mycotoxins to the lungs. 11,[20][21][22][23] In the dairy farm, the dust resulting from the handling of feedstuffs can therefore have an important role in exposure by inhalation.…”
Section: Discussionmentioning
confidence: 99%
“…11 Mycotoxins are not volatile, so airborne dust and fungal spores and fragments act as carriers of mycotoxins to the lungs. 11,[20][21][22][23] In the dairy farm, the dust resulting from the handling of feedstuffs can therefore have an important role in exposure by inhalation. Concerning dermal contact, because workers normally handle the feedstuffs with their naked hands, it is important to consider that several mycotoxins can be absorbed by the skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation